If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -70 = 14n Solving -70 = 14n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-14n' to each side of the equation. -70 + -14n = 14n + -14n Combine like terms: 14n + -14n = 0 -70 + -14n = 0 Add '70' to each side of the equation. -70 + 70 + -14n = 0 + 70 Combine like terms: -70 + 70 = 0 0 + -14n = 0 + 70 -14n = 0 + 70 Combine like terms: 0 + 70 = 70 -14n = 70 Divide each side by '-14'. n = -5 Simplifying n = -5
| 12(600)=x | | 2(-3x+5)-6x=-3(x+4) | | 14-5x+9x=-2(-7x+3) | | 8n-17=0 | | x^2-2xy+8=0 | | x-9=3x+15 | | -9x+1=2x-8 | | 3(y-6)=8y+22 | | P-3=11 | | 7+4=27 | | 6x+9=-4 | | N-3=-21 | | 2cosx=2-3sinx | | N-3=-23 | | -5w+3(w+5)=27 | | N^2+3n-128=0 | | K+12=1 | | 30-10x=-7(6-x) | | 7h+9=32 | | 19=a+1 | | 6p-6+40p=2+34p | | 6x+5-8x=-(2x-5) | | 1 = m3– 1 | | 7y-5-5y+2=0 | | 440x+25=230 | | Y=3x^2+17x+22 | | 25x+440=230 | | 2(x+4)-3=3(2x-3)+15 | | 30-10x=-7(x-6) | | 2x-6=59-11x | | 22-55+(85+65)=5 | | 25+3x=37 |